Evaluation of Government Policy Implementation in the Provision of Covid 19 Incentives in Indonesia: Systematic Review - Marianus Ruba; Ede Surya Darmawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Online learning and working from home for educators are changes that must be made by lecturers to keep teaching students. Distance education has the aim of increasing the quality of education and the relevance of education and increasing equitable access and expansion of education. Systematic review using database: Google Scholar. The search results that meet the criteria are then analyzed for articles. A systematic search yielded eight articles that best fit the study objectives. Studies vary greatly in study design, perspective, and also on the results of the evaluation of the COVID-19 health worker incentive policy. The covid 19 incentive program for health workers can be a solution to improve the performance of health workers in health services. The problem of delays, regulatory problems and also the availability of the budget are things that need to be evaluated at a later date. So that the success of the program can be a reflection of the government's success in handling COVID-19.